Overseas Returnee Executives and Digital Transformation of Enterprises: From the Perspective of Executive Compensation Gap and Executive Overconfidence - Huang, Qi; Xu, Yuhang; Tu, Shiming (Transactions on Economics, Business and Management Research, 2024)
This article selects panel data of A-share listed companies in Shanghai and Shenzhen from 2013 to 2022, uses a fixed effects model to study the relationship between overseas returnee executives and digital transformation of enterprises, and analyzes the moderating effects of executive compensation gap and executive overconfidence. The research results indicate that overseas returnee executives can significantly promote the digital transformation of enterprises; The salary gap and overconfidence of executives play a negative moderating role in the positive relationship between overseas returnees executives and digital transformation of enterprises; Heterogeneity analysis shows that overseas returnee executives have a greater impact on high-tech enterprises, low marketization areas, and enterprises in the eastern region than on non-high-tech enterprises, high marketization areas, and enterprises in the central and western regions. To better solve the problems of "not being able to transform", "unwilling to do", and "afraid to transform" in the process of enterprise digital transformation, firstly, it is necessary to effectively utilize the high-quality human resources of overseas returnee executives and provide them with reasonable care and support to better play their role; The second is to optimize the executive compensation structure and strengthen the correlation between compensation and performance; The third is to pay attention to leadership training and psychological counseling for executives, and ensure objective analysis and sufficient discussion in the decision-making process of digital transformation.